Alat Pendeteksi Kebakaran Menggunakan SMS - Sindi Permata Sari; Oriza Candra; Jhefri Asmi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Lately, there are frequent fires caused by human factors. Because we cannot predict the process of fire in advance. And the delay in knowing the occurrence of a fire is very fatal to the safety of human life and property. With advances in technology, we can overcome fires by making early fire detection devices. With the presence of temperature and smoke detectors, we can detect fires as early as possible and be delivered quickly via alarms and SMS gateways. The main component of this fire detector is the Arduino Uno. This Arduino uno acts as the brain of the fire detection device. This tool works based on the detection of the temperature condition by the DHT11 temperature sensor, which is when the temperature is above normal, an alert notification will be sent via the SMS gateway and so will the MQ2 smoke and the buzzer will sound as a warning alarm.